Young, Christian, far-right? The Identitarian movement and its relationship to Christianity - Alice Blum (IU Internationale Hochschule, 2024)
This article looks at Germany's so-called "new right" and its interpretation of religion, using the example of the "Identitarian movement" in Germany. For this purpose, it will collate previous research findings and supplement them with material from my ethnographic research on Identitarians in Germany. It will examine how, due to the demarcation from Islam, an identity-oriented "self"-image with regard to Christianity is negotiated by members within the movement. Using the example of people I have encountered in my research I investigate the extent to which Christianity is referred to and which ways of dealing with it can be classified.
Keywords: 300; Identitarian Movement; New Right; Far Right; Religion Christianity; Ethnography